Cluster-based agricultural development: A comparison between China and Africa - Zhang, Xiaobo (Wageningen Academic Publishers, 2023)
Clusters for high-value crops are ubiquitous in China and in African countries. Drawing from three case studies (potato cluster in China, medicinal and aromatic cluster in Egypt, and dates cluster in Tunisia), this chapter discusses the major challenges facing cluster development and the roles of different agents (e.g. entrepreneurs, business associations, and local governments). Cluster development involves supply-side or demand-side bottlenecks along the way, which are beyond the capacity of individual enterprises. Whether a cluster can develop to the next stage depends crucially upon whether the bottlenecks can be resolved. Because the bottlenecks are context- and temporal-specific, it would be impossible for a planner or outsider donor to prescribe a one-size-fits-all intervention to overcome all the binding constraints. Instead, local elites, such as business leaders and local officials, can play a greater role in identifying the emerging bottlenecks and figuring out indigenous solutions. In China, because local governments have an embedded interest in promoting local economic development, they are keen to provide local public goods or initiate joint actions to address the successive binding constraints and facilitate cluster development. By comparison, the role of the local government is more muted in Africa, limiting the growth potentials of agricultural clusters.